Fuzzy Logic Based Diagnostic System for Immunodeficiency and Tumor Threat in Space - Areeba Shamsi; S. K. Jain; Sanjeev Kumar (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Fuzzy logic is now frequently utilized in medical diagnostic control systems, including diabetes, dysplasia prediction, tumor progression, and so on. Many studies have been published that use fuzzy logic models to predict the structure and content of proteins and amino acids. RBCs, neutrophils, protein, eosinophils and lymphocytes were used as input variables in a fuzzy logic-based system recently developed to identify haemorrhage and brain tumor disorders. The immune system for the preservation of the human body was designed using the projected capabilities of the Fuzzy Cognitive Map (FCM). The neuro-medical area has adopted fuzzy modeling approaches to assess the FL based on facial expressions and human behavior. As a result, an effort has been made to build a diagnosis system for immunodeficiency and tumor growth in space based on this research.